Strategi Pemberdayaan Perempuan dalam Pembangunan Sosial (Studi Kasus Perempuan di Desa Mandi Angin, Kecamatan Rawas Ilir, Kabupaten Musi Rawas Utara) - Depi Putri (Da'wa Faculty IAIN Purwokerto, 2021)
The low involvement of rural women in development aspects is a problem that has not been unraveled. so that women’s aspirations have not been fully accommodated. they need to be empowered so that they can function as subjects and objects in development, both as planners, decision-makers, implementers, and the community, and enjoy the results of development equitably. This research focuses on empowering women in social development. This research is qualitative research with a field approach. The focus of this research is women’s empowerment. This research was conducted in Mandi Angin Village, Rawas Ilir District, Musi Rawas Utara Regency. Data collection was obtained through interviews, observation, and documentation. The data analysis technique uses interactive analysis (interactive model of analysis) developed by Miles and Huberman, namely data reduction and data display. drawing conclusions (concluding drawing). Based on the results of research in Mandi Angin Village, Rawas Ilir District, North Musi Rawas Regency, the first; The people of Mandi Angin Village when viewed from the economic and social aspects, the community is at the stage of pre-prosperous families and prosperous families. Second; The poor women in this village are caused by early marriages which have very little survival and end in divorce. In addition, there is no fixed income. Third; Efforts made by the government such as providing capital or direct cash assistance (BLT) for the pandemic. There is no real, measurable, and sustainable integrated program with relevant agencies that focuses on empowering women